Wages of the poor and food price inflation: Insights from the Myanmar Household Welfare Survey in Q4 2024 - Minten, Bart; Aung, Zin Wai; Zu, A Myint; Mahrt, Kristi (International Food Policy Research Institute, 2025)
This research note examines changes in food prices and their effects on the cost of both common and healthy diets, as well as on the purchasing power of casual wages. Data on food prices and casual wage levels were collected through interviews with food vendors in rural and urban areas across Myanmar, conducted between December 2021 and December 2024 as part of the ongoing Myanmar Household Welfare Survey (MHWS).